2000
DOI: 10.1139/cjm-46-3-278
|View full text |Cite
|
Sign up to set email alerts
|

Type I nitroreductases in soil enterobacteria reduce TNT (2,4,6-trinitrotoluene) and RDX (hexahydro-1,3,5-trinitro-1,3,5-triazine)

Abstract: Abstract:Many enteric bacteria express a type I oxygen-insensitive nitroreductase, which reduces nitro groups on many different nitroaromatic compounds under aerobic conditions. Enzymatic reduction of nitramines was also docu mented in enteric bacteria under anaerobic conditions. This study indicates that nitramine reduction in enteric bacteria is carried out by the type I, or oxygen-insensitive nitroreductase, rather than a type II enzyme. The enteric bacterium Morganella morganii strain B2 with documented he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 8 publications
(8 reference statements)
0
28
0
Order By: Relevance
“…This observation is unique and to the best of our knowledge, has never been reported for aerobic RDX-degrading strains. Although type 1 oxygen-insensitive nitroreductase from Morganella morganii strain B2 is known for its ability to reduce RDX (Kitts et al 2000), this is not the case with the YH1 culture because no RDX nitroso derivatives were detected.…”
Section: Discussionmentioning
confidence: 97%
“…This observation is unique and to the best of our knowledge, has never been reported for aerobic RDX-degrading strains. Although type 1 oxygen-insensitive nitroreductase from Morganella morganii strain B2 is known for its ability to reduce RDX (Kitts et al 2000), this is not the case with the YH1 culture because no RDX nitroso derivatives were detected.…”
Section: Discussionmentioning
confidence: 97%
“…A study using 14 C-labeled RDX in a laboratory compost system showed CO 2 (56%) as well as bound and soluble products (Sublette et al, 1992). Both the nitramine explosives are transformed anaerobically in mixed cultures (Boopathy et al, 1998;Freedman and Sutherland, 1998;Funk et al, 1993;Kitts et al, 1994Kitts et al, , 2000McCormick et al, 1981;Yang et al, 1986). Where products have been identified, the familiar nitro group reduction to form nitroso congeners has been found.…”
Section: Nitramine Explosivesmentioning
confidence: 99%
“…The gene encoding diaphorase, diaA , has been cloned [13]. In addition, oxygen-insensitive (type I) NADPH nitroreductases ( nsfI ) cloned from many bacteria, particularly enterobacteria, such as Enterobacter cloacae and Morganella morganii , are also able to degrade RDX [14]. Two flavin mononucleotide-containing oxidoreductases, or xenobiotic reductase, genes xenA and xenB , have been cloned from Pseudomonas putida and P. fluorescens , respectively [15].…”
Section: Introductionmentioning
confidence: 99%